PENGARUH TALENT MANAGEMENT DAN EMPLOYEE ENGAGEMENT TERHADAP EMPLOYEE CAPABILITIES: STUDI PADA KARYAWAN PT. BINTANG WAHANA TATA - Pusriadi, Tommy; Darma, Dio Caesar (Universitas Muhammadiyah Gresik, 2020)
The purpose of this paper is to determine the effect of Talent Management and Employee Engagement on the Employee Capabilities of PT. Bintang Wahana Tata. The research was done by spreading the quesioner, while the research method using Simple Random Sampling. The t test shows that the magnitude of t for Talent Management (X1) is 4.088 and the value of t arithmetic for Employee Engagement (X2) is 4.207. all of which show larger than t table is 1,985. so the hypothesis that states Talent Management and Employee Engagement have a positive effect partially on Employee Capabilities at Company PT. Bintang Wahana Tata. F test, F calculated> F table or 36.946 > 2.70 or signification level (sig) 0.000 <0.05 so that the hypothesis that states Talent Management and Employee Engagement together affect the Employee Capabilities at Company PT Bintang Wahana Tata and coefficient of determination indicate that Talent Management and Employee Engagement contributed 43.8% to Employee Capabilities at PT. Bintang Wahana Tata.